Flexural-slip folding in buckling phases of orogenic belts: Insight into the tectonic evolution of fault splays in the East Iran orogen - Rashidi, Ahmad; Shafieibafti, Shahram; Nemati, Majid; Ezati, Maryam; Gholami, Ebrahim; Mousavi, Seyed Morteza; Derakhshani, Reza (Frontiers in Earth Science, 2023)
Introduction: The East Iran orogen has experienced multiple buckling phases resulting in the formation of strike-slip fault splays. The geometric and kinematic characteristics of these splays are influenced by folding mechanisms. This study focuses on investigating the structural characteristics and tectonic evolution model of the Khousf splay, located in the northern terminus of the Nehbandan right-lateral strike-slip fault system. Methods: Field visits and geometrical properties from map views were used to analyze the structural features of the Khousf splay. The splay was found to consist of a multi-plunging anticline and syncline, referred to as the Khousf anticline and Khousf syncline, respectively. Flexural slip was identified as a significant mechanism for the formation of these structures. Structural evidence, including parasitic folds, active folds, and strike-slip duplexes, suggested that flexural slip occurred on discrete movement horizons among the rock units. Results: Analysis of the parasitic folds in the cores and limbs of the Khousf anticline and syncline revealed M, W, Z, and S shapes, with complex slicken-line patterns observed on faults parallel to the beds at the limbs. The analysis results indicated strain partitioning and inclined left- and right-lateral transpressional zones. Shortening estimates obtained from profiles in the Shekarab inclined transpressional zone were approximately 33%, 65%, and 68% for NE-SW, N-S, and NW-SE profiles, respectively. In the Arc area, which is the core of the anticline, shortening estimates from NE-SW and N-S profiles ranged from 14% to 10%. Structural analysis of the folds in this area revealed broad, close, semi-elliptical, and parabolic shapes, suggesting that secondary folds with NW-SE axis directions have been superimposed on the first-generation folds with E-W axis directions in the Khousf refolded splay. Discussion: The findings of this study highlight the structural characteristics and tectonic evolution model of the Khousf splay in the northern terminus of the Nehbandan right-lateral strike-slip fault system. The results suggest that flexural slip played a crucial role in the formation of the multi-plunging anticline and syncline in the Khousf splay. The presence of parasitic folds and complex slicken-line patterns on faults indicate the complexity of deformation processes. The observed strain partitioning and inclined transpressional zones suggest a complex tectonic history in the study area. The superimposition of secondary folds with different axis directions on first-generation folds adds further complexity to the structural evolution of the Khousf refolded splay. Overall, this study provides new insights into the structural characteristics and tectonic evolution of the Khousf splay in the East Iran orogen.